Construction of talent teams in population medicine in China : a brief comment - Ruobing FA; Changqing WANG (Editorial Office of Chinese Journal of Public Health, 2023)
Population medicine is a medical discipline that uses and integrates the knowledge, technology, art and academic of contemporary medicine and related disciplines as the basis of public health practice to maximize the overall and long-term health benefits of the population. The construction of population medicine talent teams is in line with the strategy of reinvigorating China through human resource development, and the practice of population medicine tends to be consistent with the construction of Healthy China. In this paper, we discussed the necessity and reality of the construction of talent teams in population medicine and putted forward some considerations on the construction of talent teams in China by summarizing and drawing lessons from the relevant experience and practice of foreign countries in medical talent training.